Nonpuerperal Breast Infection - C. Miranda Casas; M. Pérez; J. C. Alados; J. Fontes; G. Orellana; J. M. Aguilar; J. A. Miranda; M. de la Rosa (Hindawi Limited, 1995)
Objective: We undertook a microbiological study of purulent specimens from women with symptomatic breast abscesses.